Pra-Rancangan Pabrik Bio-Oil dari Serbuk Kayu melalui Proses Pirolisis Cepat dengan Kapasitas 20.000 Ton/Tahun - Kamila Firda Nisa’ (Fakultas Teknik, 2026)
The increasing volume of wood processing activities in Indonesia has generated a large amount of sawdust that remains underutilized and may cause environmental issues. Sawdust contains high lignocellulosic components, making it a promising feedstock for bio-oil production through thermochemical conversion. Bio-oil is a renewable liquid fuel that can be utilized as an alternative energy source and chemical feedstock. This final project aims to design a bio-oil production plant using sawdust through a fast pyrolysis process with a production capacity of 20,000 tons per year. The plant design follows a systematic chemical engineering approach, including capacity determination, process selection, equipment design, and mass and energy balance calculations. The plant operates continuously for 330 days per year. Sawdust is prepared to a particle size of 0.3–1.5 mm and a moisture content below 8% before being fed into a fluidized bed fast pyrolysis reactor operating at 500°C and atmospheric pressure, with a vapor residence time of approximately 1,5 seconds. Nitrogen is used to maintain an inert atmosphere. The main product is bio oil, while biochar and non-condensable gases are produced as by-products. Pyrolysis vapors are separated and condensed using a multi-stage condensation system, and the products are further treated before storage.
reupload 2026 Rudi H :: Finalisasi Repositori File 10 Juni 2026_Kurnadi
Keywords: Pabrik Bio-Oil; Serbuk Kayu; Pirolisis Cepat